2017
DOI: 10.1007/s00421-017-3580-6
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nitrate supplementation enhances short but not longer duration running time-trial performance

Abstract: TT performance between conditions (2643.1 ± 324. 1 vs. 2649.9 ± 319.8 s, P > 0.05). Conclusion Acute BRJ supplementation significantly enhanced 1500 m, but not 10,000 m TT performance. These findings suggest that BRJ might be ergogenic during shorter distance TTs which allow for a high work rate, but not during longer distance TTs, completed at a lower work rate. ) supplementation on physiological functioning and exercise performance in trained runners/triathletes conducting short and longer-distance treadmill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 57 publications
4
51
2
1
Order By: Relevance
“…In the present investigation, plasma [NO2] was significantly elevated consequent to NO3 supplementation, which substantiates previous research in this area (Webb et al, 2008; Bailey et al, 2009; Vanhatalo et al, 2010, 2011; Wylie et al, 2013; Shannon et al, 2016, 2017). NO generation via L-arginine appears to be blunted in hypoxic conditions (Shaul et al, 1993; Fish et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present investigation, plasma [NO2] was significantly elevated consequent to NO3 supplementation, which substantiates previous research in this area (Webb et al, 2008; Bailey et al, 2009; Vanhatalo et al, 2010, 2011; Wylie et al, 2013; Shannon et al, 2016, 2017). NO generation via L-arginine appears to be blunted in hypoxic conditions (Shaul et al, 1993; Fish et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…However, in the present study there was no apparent difference in resting MAP assessed prior to simulated altitude exposure between BRJ and PLA. This is also similar to the findings of a recent study by our group, in which trained runners/triathletes showed no change in MAP following administration of an identical NO3 dose, despite substantial increases in plasma [NO2] (Shannon et al, 2017). Recently, Ashworth et al (2015) reported a significant positive relationship between baseline BP and the change in BP following ingestion of a high-NO3 diet.…”
Section: Discussionsupporting
confidence: 92%
“…Acute nitrate supplementation has been reported to be ergogenic in some (e.g. Lansley et al 2011;Shannon et al 2017) but not all (e.g. Kelly et al 2014) previous studies using a similar design.…”
Section: Influence Of Exercise On Skeletal Muscle Nitrate and Nitritementioning
confidence: 97%
“…Ϫ supplementation, plasma NO 2 Ϫ concentration ([NO 2 Ϫ ]) declines over the course of short duration moderate-and severe-intensity exercise (32,50), as well as during repeated sprints (51,52,59). Indeed, this decline in plasma [NO 2 Ϫ ] with time during exercise, which may reflect the use of nitrite as a "substrate" for NO production, is correlated with enhanced high-intensity exercise performance following NO 3 Ϫ supplementation (52,59).…”
Section: The Preexercise Elevation In Plasma [Nomentioning
confidence: 99%
“…Ϫ ] dynamics. Indeed, previous research has reported significant reductions in plasma [NO 2 Ϫ ] following high-intensity exercise of shorter duration (32,50,52,60). It is possible that the greater degree of hypoxia and acidosis that would be expected to develop in skeletal muscle during highintensity exercise, such as TT, compared with moderate-intensity exercise, facilitates or dictates a greater reduction of NO 2…”
Section: This Greater Rate Of Decline In Plasma [Nomentioning
confidence: 99%